Activity of Caulerpa racemosa Against Helicobacter pylori Bacteria - Jekki J. F. Kalangi; Yessie K. Lengkey; Nerni O. Potalangi; Selvana S. Tulandi; Reky R. Palandi; Ferdy A. Karauwan (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Sea grapes (Caulerpa racemosa) contain various secondary metabolites with bioactive compounds that function as antibacterial agents. This study aimed to evaluate the antibacterial activity of ethanol extract from sea grapes (Caulerpa racemosa) against Helicobacter pylori. The method used was the agar diffusion technique with paper discs at four different extract concentrations: 500 µg, 600 µg, 700 µg, and 800 µg per disc. Extraction was carried out through maceration using 96% ethanol as the solvent, and antibacterial activity was assessed based on the formation of inhibition zones around the discs. The results showed that all extract concentrations exhibited very strong inhibitory effects on the growth of H. pylori, with inhibition zones of 27.23 mm, 28.51 mm, 29.91 mm, and 31.51 mm, respectively. The higher the extract concentration, the larger the inhibition zone formed. Based on antibacterial activity categorization, Caulerpa racemosa extract demonstrates potential as a strong antibacterial agent against Helicobacter pylori.